My Life - Clinton, Bill (New York : Alfred A. Knopf, 2004)
In this autobiography, President Bill Clinton portrays himself as a global leader who decided early in life to devote his intellectual and political gifts, and his extraordinary capacity for hard work, to serving the public.
Includes Bibliographical References and Index.
Keywords: 1993-2001; poll; Autobiographies